Comparison of the management of Helicobacter pylori infection between the older and younger European populations - Jonaitis, Paulius; Nyssen, Olga P; Saracino, Ilaria Maria; Fiorini, Giulia; Vaira, Dino; Pérez-Aísa, Ángeles; Tepes, Bojan; Castro-Fernandez, Manuel; Pabón-Carrasco, Manuel; Keco-Huerga, Alma; Voynovan, Irina; Lucendo, Alfredo J; et al. (Scientific reports, 2023)
The prevalence of Helicobacter pylori remains high in the older population. Specific age-related peculiarities may impact the outcomes of H. pylori treatment. The aim of the study was to evaluate the diagnostics and effectiveness of H. pylori eradication between the younger and older European populations. "European Registry on H. pylori Management (Hp-EuReg)" data from 2013 to 2022 were analyzed. Patients were divided into older (≥ 60 years) and younger (18-59 years) groups. Modified intention-to-treat (mITT) and per-protocol (PP) analysis was performed. 49,461 patients included of which 14,467 (29%) were older-aged. Concomitant medications and penicillin allergy were more frequent among the older patients. Differences between younger and older populations were observed in treatment duration in first-line treatment and in proton pump inhibitors (PPIs) doses in second-line treatment. The overall incidence of adverse events was lower in the older adults group. The overall first-line treatment mITT effectiveness was 88% in younger and 90% in the older patients (p < 0.05). The overall second-line mITT treatment effectiveness was 84% in both groups. The effectiveness of the most frequent first- and second-line triple therapies was suboptimal (< 90%) in both groups. Optimal efficacy (≥ 90%) was achieved by using bismuth and non-bismuth-based quadruple therapies. In conclusion, the approach to the diagnostics and treatment of H. pylori infection did not generally differ between younger and older patients. Main differences were reported in the concurrent medications, allergy to penicillin and adverse events both in first- and second-line treatment. Optimal effectiveness rates were mostly achieved by using bismuth and non-bismuth-based quadruple therapies. No clinically relevant differences in the effectiveness between the age groups were observed.
Keywords: Humans; alergie; Aged; Penicillins; Bismuth; Hypersensitivity; výsledek terapie; senioři; lidé; antibakteriální látky; bismut; Proton Pump Inhibitors; Helicobacter Infections; Anti-Bacterial Agents; Helicobacter pylori; inhibitory protonové pumpy; Treatment Outcome; peniciliny; kombinovaná farmakoterapie; infekce vyvolané Helicobacter pylori; Drug Therapy, Combination